NO reduction under diesel exhaust conditions over Au/Al2O3 prepared by deposition-precipitation method - Miguel, P.; Granger, P.; Jagtap, Neelam; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dujardin, Christophe (Journal of Molecular Catalysis A-Chemical, 2010)
Gold supported on alumina was prepared by urea deposition-precipitation method and compared to silver supported on alumina for the selective catalytic reduction of NO by hydrocarbons under lean conditions. The catalyst showed activity in the reduction of NO and 100% selectivity towards N-2 in the temperature range 300-350 degrees C. At higher temperature the NO conversion decreased due to competitive oxidative reactions of the reductants. XPS analysis confirmed the good stability of gold nanoparticles deposited on alumina. Infrared studies showed the formation of various adsorbed species (formates, carboxylates, ad-NOx and cyanide) on the catalyst surface. Addition of H-2 to the feed containing decane enhanced the formation of these species on the catalyst surface as well as the catalytic activity for the NO conversion to N-2. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Deposition-precipitation; Gold; In situ IR; NO reduction; XPS

Ceria-zirconia mixed oxides as thermal resistant catalysts for the decomposition of nitrous oxide at high temperature - Esteves, P.; Wu, Y.; Dujardin, Christophe; Dongare, Mohan K.; Granger, P. (Catalysis Today, 2011)
This present study deals with the development of thermally stable catalysts for the decomposition of nitrous oxide. There is actually a growing interest to minimise the emissions of nitrous oxide (N(2)O) as side-product from nitric acid plants due to a global warming potential of approximately 300 times higher than that of CO(2). Different strategies have already been implemented at industrial scale but they are still suffering from significant drawbacks essentially associated to a poor selectivity and sometimes a short lifetime in particular when the catalytic process is inserted downstream the ammonia burner. In those critical conditions, with high residual temperature of similar to 900 degrees C, significant surface and bulk reconstructions take place and then lead to drastic losses of specific surface area and related catalytic performances in the decomposition of N(2)O to N(2). Previous investigations performed in our laboratory revealed the potentiality of zirconia particularly after yttria incorporation [Appl. Catal. B 62 (2005) 236]. Novel developments of more stable ceria-zirconia based catalysts are reported in this study. Further stabilisation and enhancement in activity have been discussed on the basis of oxygen mobility related to structural properties. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceria-zirconia based catalysts; Greenhouse gas; N(2)O catalytic decomposition; Nitric acid plant; Nitrous oxide

Deposition-precipitation versus anionic-exchange Au/Al2O3 catalysts: a comparative investigation towards the selective reduction of NOx - Nguyen, D. L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Catalysis Communications, 2012)
Catalytic properties of supported gold catalysts on gamma-Al2O3 prepared by a conventional deposition-precipitation method were compared with those obtained by anionic-exchange for the reduction of NOx by hydrocarbon under lean conditions that simulate Diesel engine exhaust gas. Interestingly, a catalytic activity enhancement is observed after thermal ageing under reactive conditions at 500 degrees C on anionic-exchanged samples which make them suitable for practical developments. On the other hand, the reverse trend is observed on the solids prepared by deposition-precipitation which deactivate at low temperature. Such changes in catalytic properties have been tentatively explained on the basis of textural and structural modifications taking place during thermal ageing under wet atmosphere. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Anionic-exchange; Au catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Promising stability of gold-based catalysts prepared by direct anionic exchange for DeNO (x) applications in lean burn conditions - Nguyen, D. -L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Topics in Catalysis, 2013)
Supported gold catalysts on gamma-Al2O3 have been investigated in the catalytic reduction of NO (x) in simulated Diesel exhaust gas conditions. Different parameters have been examined essentially the mode of gold incorporation via classical deposition-precipitation and anionic exchange methods and the nature of the pre-activation thermal treatment. The resistance to thermal ageing under reactive conditions at 500 A degrees C was found completely different with a significant rate enhancement on anionic-exchange samples. Further comparisons also show that the nature of the pre-activation thermal treatment influences the extent of surface reconstructions during thermal ageing with a detrimental effect of reductive pre-treatment on the catalytic performances.
Keywords: Anionic-exchange; Au/Al2O3 catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Activation by pretreatment of Ag-Au/Al2O3 bimetallic catalyst to improve low temperature HC-SCR of NOx for lean burn engine exhaust - More, Pavan M.; Nguyen, Duy L.; Granger, Pascal; Dujardin, Christophe; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2015)
Bimetallic Ag-Au/Al2O3 catalyst was synthesised by successive impregnation of 1% Au and 1% Ag on in-house prepared high surface area alumina (450 m(2)/g). The corresponding monometallic catalysts were also prepared by loading 1% Ag or 1% Au on the same high surface area alumina for comparison. The catalysts were characterised by various physico-chemical techniques and tested for SCR activity under lean burn engine exhaust conditions. Ag-Au/Al2O3 catalyst prepared by successive impregnation method showed considerably higher NO reduction (100%) to N-2 compared to 1% Au/Al2O3 (70%) whereas the activity was comparable with that of 1% Ag/Al2O3 (96%). The effect of various pretreatments on SCR activity of Ag-Au/Al2O3 was studied and pretreatment at 250 degrees C in flow of hydrogen was found to give the best results with 100% NO conversion to N-2 at 353 degrees C. Further ageing of the catalyst under reaction feed at 500 degrees C resulted in considerable increase in low temperature activity of bimetallic catalyst with similar to 40% NO conversion at 222 degrees C. Even though the SCR activity of pretreated Ag-Au/Al2O3 and Ag/Al2O3 were comparable, after ageing the Ag-Au/Al2O3 showed significantly higher NO conversion (95%) compared to Ag/Al2O3 (83%) and Au/Al2O3 (70%). The formation of H-2 and CO due to steam reforming of higher hydrocarbon (decane) was evidenced at the temperature of highest deNO(x) activity. Detailed investigation of the textural properties of the pretreated and aged catalysts showed presence of well dispersed metallic Au and Ag-n(delta+) clusters after pretreatment in hydrogen at 250 degrees C. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag-Au bimetallic catalyst; Catalyst ageing; dispersion; Low temperature HC-SCR; Steam reforming

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR